Developing English Language Teachers’ Action Research Competencies Through an Exploratory Action Research Project - Lakshmana Rao Pinninti (Profile: Issues in Teachers' Professional Development)
This article reports the impact of an exploratory action research (EAR) project on developing teachers’ action research competencies. Through various face-to-face and online activities, the project facilitated four English language teachers to conduct EAR in their teaching contexts. Qualitative data were collected through reflective journals and WhatsApp group chats. Data reveal that each participating teacher critically reflected on the teaching context, selected a research question, collected and interpreted evidence, designed and evaluated an action, and disseminated their research. The findings imply that teachers’ participation in EAR can develop their action-research competencies and ability to integrate teaching and research for their continuing professional development.